A Horner’s polynomial based quadrupedal multi-gaits signal generation controller - Olivier Akansie, Kouame Yann; C. Biradar, Rajashekhar; Rajendra, Karthik; D. Devanagavi, Geetha (Institute of Advanced Engineering and Science, 2024)
Animal locomotion is the process through which animals move from one location to another. Self-propelled locomotion is based on the animal performing a series of actions to move towards a predetermined target. All of these motions occur sequentially and repeat themselves during a gait cycle. A gait cycle may be simulated by duplicating each motion in the cycle sequentially. To achieve this goal, a problem known as the gait planning issue was formulated, in which various systems were created to provide suitable signals for the execution of distinct gaits (patterns of steps of an animal at a specified speed). This research approaches the problem using Horner's polynomials for quadruped robots. The approach entails first creating a sequence table for each gait and fit two polynomial equations. In this study, an attempt is made to combine several gaits using Horner's polynomials. An algorithm uses elaborated polynomials to generate the desired gaits signals.